2014
DOI: 10.1111/mpp.12207
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas corrugata crpCDE is part of the cyclic lipopeptide corpeptin biosynthetic gene cluster and is involved in bacterial virulence in tomato and in hypersensitive response in Nicotiana benthamiana

Abstract: Pseudomonas corrugata CFBP 5454 produces two kinds of cyclic lipopeptides (CLPs), cormycin A and corpeptins, both of which possess surfactant, antimicrobial and phytotoxic activities. In this study, we identified genes coding for a putative non-ribosomal peptide synthetase and an ABC-type transport system involved in corpeptin production. These genes belong to the same transcriptional unit, designated crpCDE. The genetic organization of this locus is highly similar to other Pseudomonas CLP biosynthetic cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 55 publications
1
50
0
Order By: Relevance
“…While many of the lipopeptide biosynthesis-associated genes were found in a subset of P. syringae strains, the entire set of 15 genes including the quorum sensing system were found in three other species that contain bona fide plant pathogens (P. corrugata, P. mediterranea and P. fuscovaginae sensu lato) within the P. fluorescens clade as well as several strains with known antifungal activity ( Figure 2F and Table S3). Genomic and genetic evidence from these three pathogenic species support a role for the LPQ island in pathogenesis in a variety of hosts, suggesting that the mechanism used by N2C3 to kill Arabidopsis may be conserved in divergent strains throughout the P. fluorescens clade 7,8,[39][40][41][42] . Additionally, it was previously shown that the LPQ island is the source of antifungal cyclic lipopeptides in two other strains (DF41 and in5) 43,44 .…”
Section: A Pathogenicity Island Found In Plant-associated P Fluorescensmentioning
confidence: 95%
“…While many of the lipopeptide biosynthesis-associated genes were found in a subset of P. syringae strains, the entire set of 15 genes including the quorum sensing system were found in three other species that contain bona fide plant pathogens (P. corrugata, P. mediterranea and P. fuscovaginae sensu lato) within the P. fluorescens clade as well as several strains with known antifungal activity ( Figure 2F and Table S3). Genomic and genetic evidence from these three pathogenic species support a role for the LPQ island in pathogenesis in a variety of hosts, suggesting that the mechanism used by N2C3 to kill Arabidopsis may be conserved in divergent strains throughout the P. fluorescens clade 7,8,[39][40][41][42] . Additionally, it was previously shown that the LPQ island is the source of antifungal cyclic lipopeptides in two other strains (DF41 and in5) 43,44 .…”
Section: A Pathogenicity Island Found In Plant-associated P Fluorescensmentioning
confidence: 95%
“…A gene dptR2, encoding a DeoR-type regulator located close to the daptomycin biosynthesis gene cluster was found essential for daptomycin production . Also, in Pseudomonas corrugata, the genes encoding NRPS and an ABC-type transport system for lipopeptide corpeptin, belonged to the same transcriptional unit (Strano et al 2015). The genome of B. subtilis 916 has four NRPS gene clusters such as srf, bmy, fen, and loc, for biosynthesis of surfactins, bacillomycin L, fengycins, and locillomycins, respectively (Luo et al 2015).…”
Section: Biosynthetic Mechanismsmentioning
confidence: 99%
“…Further, it exerted cytotoxicity towards human melanoma A375 cells mediated by plasma membrane permeabilization (Janek et al 2013). Apart from the above mentioned cyclic lipopeptides, there are many other cyclic lipopeptides with potential roles in medical fields which include Bacillus licheniformis-elaborated lichenysin (Nerurkar 2010), Bacillus subtilis SSE4-elaborated subtulene A (Thasana et al 2010), Paenibacillus kobensis M-elaborated mattacin (Martin et al 2003), Paenibacillus tianmuensis-elaborated battacin (Qian et al 2012b), Paenibacillus elgii-elaborated pelgipeptin (Qian et al 2012a), Micromonospora-elaborated rakicidin (Takeuchi et al 2011), Actinoplanes friuliensis HAG 010964-elaborated friulimicin (Schneider et al 2009;Rückert et al 2014), Serratia marcescens-elaborated serrawettin W1 (Thies et al 2014), Pseudomonas corrugata CFBP 5454-elaborated corpeptins (Strano et al 2015), Pseudomonas fluorescens SS101-elaborated massetolide (Song et al 2014) etc. In fact, the list is exhaustive and it reflects the rationale of searching for novel lipopeptides.…”
Section: Pseudofactinmentioning
confidence: 99%
“…In various other Pseudomonas species and strains, regulatory genes encoding similar LuxR‐like proteins are positioned up‐ and downstream of the CLP biosynthesis genes (De Bruijn & Raaijmakers, 2009a). Within several CLP families, the regulation of CLP biosynthesis has been attributed to LuxR‐type regulators including PsoR (putisolvin) in P. putida (Dubern et al., ), ViscA and ViscBC (viscosin) in P. fluorescens SBW25 (De Bruijn & Raaijmakers, 2009a), MassA and MassBC (massetolide) in P. fluorescens SS101 (De Bruijn & Raaijmakers, 2009b), ArfF (arthrofactin) in P. fluorescens MIS38 (Washio et al., ), EtlR (entolysin) in P. entomophilia L48T (Vallet‐Gely et al., ), WlpR (WLIP) in P. putida RW10S2 (Rokni‐Zadeh et al., ), XtlR (xantholysin) in P. putida BW11M1 (Li et al., ), and PcoR and RfiA (corpeptin) in P. corrugata CFBP 5454 (Strano et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In various other Pseudomonas species and strains, regulatory genes encoding similar LuxR-like proteins are positioned up-and downstream of the CLP biosynthesis genes (De Bruijn & Raaijmakers, 2009a). Within several CLP families, the regulation of CLP biosynthesis has been attributed to LuxR-type regulators including PsoR (putisolvin) in P. putida (Dubern et al, 2008), ViscA and ViscBC (viscosin) , and PcoR and RfiA (corpeptin) in P. corrugata CFBP 5454 (Strano et al, 2015).…”
mentioning
confidence: 99%